The COVID-19 pandemic: implications for the head and neck anesthesiologist. Issue 3 (19th August 2020) - Healy, David W.; Cloyd, Benjamin H.; Brenner, Michael J.; Kupfer, Robbi A.; Anam, Karina S.; Schechtman, Samuel A.
Abstract : Purpose: As the COVID-19 pandemic has unfolded, there has been growing recognition of risks to the anesthesia and surgical teams that require careful consideration to ensure optimal patient care. Airway management and other head and neck procedures risk exposure to mucosal surfaces, secretions, droplets, and aerosols that may harbor the SARS-CoV-2 virus. This review provides guidance on optimal practice approaches for performing patient evaluation and management of head and neck procedures with the shared goal of providing safe and effective patient care while minimizing the risk of viral transmission. Methods: The scientific literature was evaluated, focusing on strategies to reduce risk to health care workers involved in airway management and head and neck surgery. The search strategy involved curating consensus statements and guidelines relating to COVID-19 or prior coronavirus outbreaks in relation to aerosol-generating procedures (AGPs) and other high-risk procedures, with the search restricted to the scope of head and neck anesthesia. A multidisciplinary team analyzed the findings, using iterative virtual communications through video conference, telephone, email, and shared online documents until consensus was achieved, loosely adapted from the Delphi technique. Items without consensus were so indicated or removed from the manuscript. Results: Health care worker infection and deaths during the COVID-19 pandemic and prior outbreaks mandate robust standards for infection control. Most head and neck anesthesiology procedures generate aerosols, and algorithms may be modified to mitigate risks. Examples include preoxygenation before induction of anesthesia, rapid sequence induction, closing circuits expeditiously, and consideration of apneic technique for surgical entry of airway. Rescue measures are also modified, with supraglottic airways elevated in the difficult airway algorithm to minimize the need for bag mask ventilation. Personal protective equipment for AGPs include fit-tested N95 mask (or purified air positive respirator), gloves, goggles, and gown for patients with known or suspected COVID-19. Meticulous donning and doffing technique, minimizing personnel and room traffic, diligent hand hygiene, and social distancing all can decrease risks. Perioperative management approaches may differ from commonly employed patterns including avoidance of techniques such as jet ventilation, high-flow nasal oxygen and instead utilizing techniques with a closed ventilatory circuit and secured endotracheal tube, minimizing open suctioning, and preventing aerosolization at emergence. Recommendations are made for the following head and neck procedures and considerations: primary airway management; high-flow nasal oxygen delivery; jet ventilation for laryngotracheal surgery; awake intubation; transnasal skull base surgery; tracheostomy; and use of personal protective equipment. COVID-19 testing may facilitate decision making, but it is currently often unavailable and urgency of surgical treatment must be considered. Conclusions: During pandemics, head and neck anesthesia and surgical teams have a duty to not only provide high quality patient care but also to ensure the safety of the health care team. Several specific perioperative approaches are recommended that have some variance from commonly employed practices, focusing on the reduction of AGP to minimize the risk of infection from patients with known or suspected COVID-19 infection.